A study of medical students’ perceptions of their learning environment - Parajuli, SR; Acharya, CP; Manandhar, V; Rajbanshi, R (Devdaha Medical Journal, 2025)
Introduction: The learning environment within an institution encompasses the academic atmosphere experienced by both students and educators, which significantly influences learning outcomes. A positive learning environment promotes engagement, collaboration, and professional growth. The Dundee Ready Education Environment Measure (DREEM) is a globally recognized tool for evaluating educational climates in health professions education. This study utilized the DREEM-12 questionnaire to assess medical students’ perceptions of their learning environment at Manipal Teaching Hospital. Methods: A cross-sectional study was conducted among 175 undergraduate MBBS students from different academic years. Participants completed the DREEM-12 questionnaire via Google Forms. Domain scores were calculated by summing individual item responses, and overall scores were interpreted based on established guidelines. Results: The study included nearly equal proportions of male (45.7%) and female (54.3%) participants, with a mean age of 22.4 ± 2 years (range: 18–27). The mean scores for each domain were as follows: Students’ Perception of Learning (SPL): 5.4 ± 1.9, Students’ Perception of Teachers (SPT): 7.1 ± 2.6, Students’ Academic Self-Perception (SASP): 7.6 ± 2.4, Students’ Perception of Atmosphere (SPA): 4.2 ± 2.1, Students’ Social Self-Perception (SSSP): 3.4 ± 2.1. The total mean score was 27.7 ± 8.9, indicating a "more positive than negative" perception. Conclusion: Students generally viewed their learning environment favorably, though perceptions varied by academic year. Clinical-year students reported greater challenges than their pre-clinical peers, suggesting that evolving academic pressures influence their experiences. Despite these differences, students maintained confidence in their academic abilities.